Characterization of Polyploid Embryoid Lines Induced via Unfertilized Ovule Culture of Loquat (Eriobotrya japonica Lindl.) - Shuming Wang; Tingting Ruan; Yin Zhang; Peng Wang; Jiangbo Dang; Yan Xia; Danlong Jing; Guolu Liang; Qigao Guo; Qiao He (Horticulturae, 2025)
Polyploidy plays a significant role in loquat breeding, particularly in triploid breeding for seedless fruit production. Currently, loquat polyploid breeding primarily relies on natural seedling selection and sexual hybridization approaches. In this study, unfertilized ovules from four loquat varieties were in vitro cultured. Gynogenesis and embryoid regeneration were achieved in ‘Xingning 1’ and ‘Huabai 1’, with ‘Xingning 1’ demonstrating the highest gynogenesis efficiency (21.63%). Flow cytometry and chromosome counting revealed that the obtained embryoid lines included haploid, diploid, tetraploid, hexaploid, and chimeric ploidy types. Further characterization of ‘Xingning 1’-derived embryoid lines through SSR markers and whole-genome resequencing confirmed that the haploid, diploid, tetraploid, and hexaploidy embryoid originated from haploid–somatic chimeras, diploid, doubled diploid and tripled diploid, respectively. Metabolic analysis showed a positive correlation between ploidy level and the content of both soluble sugars and organic acids. This study explored a novel platform for polyploid induction in loquat and may provide methodological insights for improvement of other perennial fruit trees.